Alpha-Lipoic Acid Is an Effective Nutritive Antioxidant for Healthy Adult Dogs - Reshma M. Anthony; Jennifer M. MacLeay; Dennis E. Jewell; John J. Brejda; Kathy L. Gross (Animals, 2021)
This study was designed to determine the effect of alpha-lipoic acid on the glutathione status in healthy adult dogs. Following a 15 month baseline period during which dogs were fed a food containing no alpha-lipoic acid, dogs were randomly allocated into four groups. Groups were then fed a nutritionally complete and balanced food with either 0, 75, 150 or 300 ppm of alpha-lipoic acid added for 6 months. Evaluations included physical examination, body weight, food intake, hematology, serum biochemistry profile and measurements of glutathione in plasma and erythrocyte lysates. Throughout, blood parameters remained within reference ranges, dogs were healthy and body weight did not change significantly. A significant increase of 0.05 ng/mL of total glutathione in red blood cell (RBC) lysate for each 1 mg/kg bodyweight/day increase in a-LA intake was observed. In addition, a significant increase was observed for GSH, GSSG and total glutathione in RBC lysate at Month 6. We conclude that alpha-lipoic acid, as part of a complete and balanced food, was associated with increasing glutathione activity in healthy adult dogs.